Avascular bone necrosis of the femoral head after renal transplantation: Is it avoidable? - Refaie, Ayman F; Abd El-Gawad, Zeyad; Fouda, Mohamed A; Hamdy, Ahmed F; Bakr, Mohamed A; Mostafa, Amani; Abo El Ghar, Mohamed I; Refaie, Huda F; Bahgat, Sameh; El Shahawy, El Metwaly; Ghoneim, Mohamed A (African Journal of Nephrology, 2010)
<p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Background: Avascular osteonecrosis (AVN) is a seriousosseous complication after renal transplantation (RT). Itsprevalence clearly decreased from 20% to 4% possiblydue to the use of calcinurin inhibitors (CNI), reduction ofsteroid doses and use of steroid free regimens. The aimof our study was to evaluate the frequency of AVNamong our kidney transplant recipients and to determinethe risk factors for its occurrence. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Patients and methods: Among 1785 kidney transplantrecipients who received renal allografts between March1976 and December 2005, 40 patients (2.24%) developedAVN with a mean age of 31.3 10.2 years. Eightykidney transplant recipients without AVN were selectedto be a matched control group. The localization of AVNwas the femoral head in all cases. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Results: AVN was diagnosed at a mean of 20.4 monthsafter transplantation. The following risk factors werestatistically significant; sirolimus-based regimen,hypercholesterolemia, overweight with body mass index(BMI)>26 and those with HLA A9, HLA B35 and DRB15. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Conclusions: We concluded that the proper managementof hypercholesterolemia, maintenance of ideal bodyweight as well as avoidance of sirolimus-basedimmunosuppressive regimen in genetically predisposedpatients may be an effective preventive strategy to avoidAVN.